The future is now : an introduction to prefigurative politics - Monticelli, Lara; Escobar, Arturo, 1951- (Alternatives to Capitalism in the 21st Century, 2022)
This edited collection analyses the unique characteristics of urban gardens, worker-owned coops, ecological communities, occupied factories and other social movements to demonstrate what we can learn from them in order to rethink our economies and societies.